Machiavellianism, Internal Locus of Control, and Time Pressure as Correlates of Dysfunctional Audit Behavior at a Government Inspectorate - Zakia Amanda Zais; Mazda Eko Sri Tjahjono; Sabaruddinsah (International Journal of Economics, Business Management and Accounting (IJEBMA), 2026)
Dysfunctional audit behavior can weaken evidence quality and public accountability. This study examines the associations of machiavellianism, internal locus of control, and time pressure with dysfunctional audit behavior among government internal-audit personnel in Banten Province, Indonesia. An attempted census invited 110 eligible personnel and produced 71 usable questionnaires collected from 8 to 22 April 2026. Multiple regression yielded a significant model, F (3, 67) = 21.009, p < .001, R² = .485. Machiavellianism (β = .300, p = .005) and time pressure (β = .496, p < .001) were positively associated with dysfunctional behavior, whereas internal locus of control was not significant (β = -.021, p = .824). Inspectorates should combine ethical supervision with realistic workload and time-budget controls.